2022
DOI: 10.1186/s12891-022-05430-6
|View full text |Cite
|
Sign up to set email alerts
|

Could radiofrequency echographic multispectrometry (REMS) overcome the overestimation in BMD by dual-energy X-ray absorptiometry (DXA) at the lumbar spine?

Abstract: Background Osteoarthritis (OA) and vertebral fractures at the lumbar spine lead to an overestimation of bone mineral density (BMD). Recently, a new approach for osteoporosis diagnosis, defined as radiofrequency echographic multi-spectrometry (REMS), represents an innovative diagnostic tool that seems to be able to investigate bone quality and provide an estimation of fracture risk independent of BMD. The aim of this paper was to evaluate whether the use of REMS technology can fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Moreover, these data also reported comparable results between the fracture risk estimates derived by the two technologies. Furthermore, our data supports the robustness of the REMS technique against the influence of AOCs when assessing the lumbar spine BMD, as already suggested in recent case series [19] and in a cross-sectional study [20]. On the contrary, as already shown in previous studies [10,11], AOCs predispose to an artefactual increase in lumbar spine BMD when measured with the commonly adopted anteroposterior approach, with the consequent risk of obtaining a misleading T-score value.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, these data also reported comparable results between the fracture risk estimates derived by the two technologies. Furthermore, our data supports the robustness of the REMS technique against the influence of AOCs when assessing the lumbar spine BMD, as already suggested in recent case series [19] and in a cross-sectional study [20]. On the contrary, as already shown in previous studies [10,11], AOCs predispose to an artefactual increase in lumbar spine BMD when measured with the commonly adopted anteroposterior approach, with the consequent risk of obtaining a misleading T-score value.…”
Section: Discussionsupporting
confidence: 90%
“…These findings confirm REMS technology’s capability not only to address artifacts related to osteoarthritis but also those associated with spondylitis, vertebral fractures, and vertebroplasty or kyphoplasty operations. This capability enhances the accuracy of osteoporosis diagnosis and, consequently, a better definition of fragility fracture risk [ 21 , 22 ]. However, it’s important to note that the absence of published data on the accuracy of REMS in individuals with a BMI greater than 40 kg/m 2 may represent a limitation in the use of REMS in severely obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a few preliminary reports have documented that REMS technology is able to improve the accuracy of the diagnosis of osteoporosis in cases where lumbar BMD by DXA is impaired by the presence of artifacts from vertebral fractures or osteoarthritis [ 21 , 22 , 23 ]. Therefore, on the basis of these preliminary data, we conducted the DEMETER study.…”
Section: Introductionmentioning
confidence: 99%
“…European studies have confirmed the diagnostic precision and reliability of REMS versus DXA [96,97]. An Italian study conducted on a white female population demonstrated that REMS effectively addressed common DXA artifacts, such as OA and vertebral fractures [98]. Ishizu et al found that proximal femur BMD measurements obtained via REMS were significantly lower than those obtained via DXA, while a significant correlation was observed between the HOA Kellgren-Lawrence grade and proximal femoral T-score discrepancies.…”
Section: Diagnosismentioning
confidence: 96%